Philosophy 167: Class 3 - Part 12 - Astronomia Nova, Part 4: the Diametral Distance Rule, and Settling on the Ellipse. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Shows how Kepler derived the elliptical shape of orbits.; Opening line: "Okay, then he notices something that really strikes him and I'll just read it. The breadth of the lunule of Chapter 46 above."; Duration: 11:49 minutes.; Segment: Class 3, Part 12.